Adapted dandelions trade dispersal for germination upon root herbivore attack. Issue 1921 (26th February 2020) - Bont, Zoe; Pfander, Marc; Robert, Christelle A. M.; Huber, Meret; Poelman, Erik H.; Raaijmakers, Ciska E.; Erb, Matthias
Abstract : A plant's offspring may escape unfavourable local conditions through seed dispersal. Whether plants use this strategy to escape insect herbivores is not well understood. Here, we explore how different dandelion ( Taraxacum officinale agg.) populations, including diploid outcrossers and triploid apomicts, modify seed dispersal in response to root herbivore attack by their main root-feeding natural enemy, the larvae of the common cockchafer Melolontha melolontha. In a manipulative field experiment, root herbivore attack increased seed dispersal potential through a reduction in seed weight in populations that evolved under high root herbivore pressure, but not in populations that evolved under low pressure. This increase in dispersal potential was independent of plant cytotype, but associated with a reduction in germination rate, suggesting that adapted dandelions trade dispersal for establishment upon attack by root herbivores. Analysis of vegetative growth parameters suggested that the increased dispersal capacity was not the result of stress flowering. In summary, these results suggest that root herbivory selects for an induced increase in dispersal ability in response to herbivore attack. Induced seed dispersal may be a strategy that allows adapted plants to escape from herbivores.